Vascular endothelial growth factor attenuates neointimal hyperplasia of decellularized small-diameter vascular grafts by modulating the local inflammatory response - Xie, Xinlong; Wu, Qiying; Liu, Yuhong; Chen, Chunyang; Chen, Zeguo; Xie, Chao; Song, Mingzhe; Jiang, Zhenlin; Qi, Xiaoke; Liu, Sixi; Tang, Zhenjie; Wu, Zhongshi (Frontiers in Bioengineering and Biotechnology, 2022)
Small-diameter vascular grafts (diameter <6mm) are in high demand in clinical practice. Neointimal hyperplasia, a common complication after implantation of small- diameter vascular grafts, is one of the common causes of graft failure. Modulation of local inflammatory responses is a promising strategy to attenuates neointimal hyperplasia. Vascular endothelial growth factor (VEGF) is an angiogenesis stimulator that also induces macrophage polarization and modulates inflammatory responses. In the present study, we evaluated the effect of VEGF on the neointima hyperplasia and local inflammatory responses of decellularized vascular grafts. In the presence of rhVEGF-165 in RAW264.6 macrophage culture, rhVEGF-165 induces RAW264.6 macrophage polarization to M2 phenotype. Decellularized bovine internal mammary arteries were implanted into the subcutaneous and infrarenal abdominal aorta of New Zealand rabbits, with rhVEGF-165 applied locally to the adventitial of the grafts. The vascular grafts were removed en-bloc and submitted to histological and immunofluorescence analyses on days 7 and 28 following implantation. The thickness of the fibrous capsule and neointima was thinner in the VEGF group than that in the control group. In the immunofluorescence analysis, the number of M2 macrophages and the ratio of M2/M1 macrophages in vascular grafts in the VEGF group were higher than those in the control group, and the proinflammatory factor IL-1 was expressed less than in the control group, but the anti-inflammatory factor IL-10 was expressed more. In conclusion, local VEGF administration attenuates neointimal hyperplasia in decellularized small-diameter vascular grafts by inducing macrophage M2 polarization and modulating the inflammatory response.